Analisis Proses Pembinaan dan Monitoring Sekolah Menengah Pertama oleh Bidang Pembinaan SMP Dinas Pendidikan Kota Palangka Raya - Sephia Sephia; Slamet Riyadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the coaching and monitoring processes implemented by the Junior High School (SMP) Development Division at the Palangka Raya City Education Office. The study focuses on the forms of coaching activities, monitoring mechanisms, and the effectiveness of both programs in supporting educational quality improvement at the junior high school level. This study uses a descriptive qualitative approach using observation, interviews, and documentation methods. Data were obtained through the author's direct involvement during an internship in the Junior High School Development Division. The results indicate that the implementation of coaching and monitoring has been structured through routine programs such as school supervision, principal mentoring, education data verification, and coordination for teacher competency improvement. However, obstacles were also identified, such as limited human resources, suboptimal communication between schools, and uneven implementation of monitoring across the region. Therefore, strengthening the coordination system and digitizing monitoring is necessary to ensure the coaching process is more effective, efficient, and sustainable. This research provides an empirical contribution to efforts to improve the quality of educational services at the junior high school level and serves as a reference for developing school development policies in the region.